Clear cell sarcoma of vulva. A case report - Němejcová, Kristýna; Dundr, Pavel; Krajsová, Ivana (Ceskoslovenska patologie, 2016)
We report the case of a 67-year-old female with clear cell sarcoma (CCS) of the vulva. Grossly, the tumor was a partly exophytical vulvar mass, measuring 20 x 15 cm. At the time of presentation, the patient showed metastases to the lung, inguinal and pelvic lymph nodes. Histologically, the tumor consisted of oval or spindle cells with only mild nuclear pleomorphism and rare mitoses (up to 2/10 HPF). The cytoplasm was pale eosinophilic or clear. The tumor cells were arranged in confluent sheets. There were large areas of necrosis and surface ulceration. Immunohistochemically, the tumor cells showed expression of S-100 protein and focal melan A and HMB45 expression. Fluorescent in situ hybridization analysis revealed rearrangement of the EWSR1 gene. To the best of our knowledge, this is the first report of CCS arising in the vulva.
Keywords: senioři; diferenciální diagnóza; Sarcoma, Clear Cell; hybridizace in situ fluorescenční; sarkom z jasných buněk; lidé; vulva; Vulva; clear cell sarcoma - EWSR1 gene - melanoma of soft parts - vulva.; In Situ Hybridization, Fluorescence; proteiny S100; ženské pohlaví; Humans; S100 Proteins; Diagnosis, Differential; Female; Aged; Vulvar Neoplasms; nádory vulvy